ANALYSIS OF BIOLOGICALLY ACTIVE PROPERTIES OF SERRATULA CORONATA L., GROWING IN THE REGIONS OF NORTHERN KAZAKHSTAN (KOKCHETAV UPLANDS) (Experimental biology, 2024)
Serratula coronata L. is known in folk medicine as an astringent, choleretic, anti-inflammatory, antifever, antiemetic and sedative. The article presents the results of studies assessing the phytocenotic state and biological activity of Serratula coronata L., growing in Northern Kazakhstan (Kokchetav Upland). The antibacterial and antifungal activities of Serratula coronata L. against strains of bacteria Escherichia coli, yeast Candida parapsilosis, and mould fungi Aspergillus niger were studied using microbiological methods. An alcohol tincture and an aqueous decoction of the roots of Serratula coronate L. were distinguished by antibacterial activity, which suppressed the growth of E. coli to a dilution of 1:512 (alcohol tincture), 1:8 (aqueous decoction). Aqueous extracts of Serpukha crowned have pronounced bacteriostatic properties against E. coli.An aqueous infusion of the roots of Serratula coronate L. was found to have fungicidal activity against the yeast C. parapsilosis, while an alcoholic infusion of the roots of the plant, showed fungicidal and fungistatic activity against the opportunistic mould fungi A. niger when diluted, to 1:8.Oily and hydroalcoholic extracts of above-ground and underground vegetative organs of Serratula coronata L. have pronounced antiparasitic activity. At the same time, the intensity of antiparasitic properties is higher in aqueous-alcoholic extracts of the above-ground organs of Serpukha crowned.It has been established that Serratula coronate L. can successfully be used as a raw material for producing veterinary and pharmaceutical drugs and food and feed additives.
Keywords: crowned serpukha (Serratula coronata L.), Kokchetav upland; bactericidal; fungicidal; antiparasitic effect; pharmaceutical potential